Reclamation Plan on Stone Land of The Ex-Nickel Mining at PT Vale Indonesia Tbk Central Pinnacle Condemnation - Muhammad Furqan Al Faruqi; Firman Nullah Yusuf; Habibie Anwar; Alam Budiman Thamsi (CV Insight Publisher, 2023)
Environmental and occupational safety issues in the world's mining business have always been the most important issues. The main problems that arise in ex-mining areas include environmental changes which include chemical changes, physical changes and biological changes (Hoskin, 2002). Reclamation is an activity carried out throughout the stages of the mining business to organize, restore and improve the quality of the environment and ecosystem so that they can function again according to their designation (Ahmad, 2006). Primary data collection was obtained using a mobile phone as evidence of the implementation of research activities for research location data, reclamation locations were taken using GPS (global position system) and drones. Secondary data is given directly from supervisors in the company. Land arrangement is intended to obtain a surface finish that is stable and has a natural shape so that it is in harmony with the shape of the pristine landscape, supports the success of plant growth, facilitates access to further work throughout the area, and increases the aesthetic value of the land (Munir, 2017). All irregular heaps are tidied up and leveled, deposits that have the potential to form a collection of water are filled with the result of pushing material from the leveled heap. Ex-mining land with irregular and uneven terrain (holes, relatively steep slopes) must be laid out in such a way as to be stable with low landslide and erosion hazard potential (Noor Rizqoon, 2004). Piling of rocks using top soil as thick as 50 cm on rocky ground. Activities that are no less important are sowing topsoil, making contour drains and making planting holes, these activities are carried out by making arrangements for making drainage and pocket ponds have been completed. Planting holes with a spacing of 3.5 meters and 4 meters can be ascertained that in 1 hectare of reclamation land for Konde Central Pinnacle 714 planting holes can be made, so it can be concluded that the planting holes for Konde Central Pinnacle are good with spacings of 3.5m and 4m.